ANALISIS HERDING BEHAVIOR PADA SEKTOR SEKTOR YANG TERDAFTAR DI BURSA EFEK INDONESIA DAN BURSA SAHAM MALAYSIA TAHUN 2015 2021 - David Kaluge; Ivan Purnama Putera (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The growth of investors in the Indonesian capital market has grown significantly over the past five years. However, this was followed by a fairly slow growth in financial literacy, especially in the capital market sector. The existence of inequality in the growth of these two things can lead to irrational investors because investors who have good literacy will make better investment decisions by doing analysis. One of the irrational behavior as a result of this inequality is herding behavior. In addition, the COVID-19 pandemic which caused panic among investors in the capital market also encouraged herding behavior. This study aims to analyze and detect herding behavior on the Indonesia Stock Exchange and the Malaysia Stock Exchange by dividing it into three different periods, namely before the pandemic, during the pandemic, and after the COVID-19 pandemic. The method used to detect herding behavior in this study is Cross. Sectional Absolute Deviation (CSAD) introduced by Chang et al. (2000) using the rolling regression method. The results showed that the intensity level of herding behavior was very high during the COVID-19 pandemic or in 2020 on the Indonesia Stock Exchange and the Malaysian Stock Exchange. In addition, for the entire study period, the intensity level of herding behavior on the Malaysian Stock Exchange is higher than the Indonesian Stock Exchange.